2012
DOI: 10.1111/j.1469-8986.2012.01383.x
|View full text |Cite
|
Sign up to set email alerts
|

The interaction of electrodermal activity and expressed emotion in predicting symptoms in recent‐onset schizophrenia

Abstract: In the present study, expressed emotion (EE) was assessed among immediate family members of 94 recent-onset schizophrenia patients at initial study entry point, and patients' electrodermal activity (EDA) was measured without the presence of family members at a baseline outpatient stabilization assessment. Psychiatric symptoms were also rated, both at the baseline outpatient test, and at one-year follow-up. Electrodermal Activity × Expressed Emotion interactions were observed at both test points. In each case, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 38 publications
(42 reference statements)
1
8
0
1
Order By: Relevance
“…Higher child physiological reactivity may not only be a potential outcome of high EE, but may also make certain children more vulnerable to (i.e., moderate) the negative effects of EE. Indeed, a recent study found that negative symptoms in adults with schizophrenia were particularly elevated when higher EE environments were paired with greater electrodermal reactivity (EDA) in the individual (Subotnik et al, 2012).…”
Section: Moderators Of Criticism-behavior Problem Linksmentioning
confidence: 99%
“…Higher child physiological reactivity may not only be a potential outcome of high EE, but may also make certain children more vulnerable to (i.e., moderate) the negative effects of EE. Indeed, a recent study found that negative symptoms in adults with schizophrenia were particularly elevated when higher EE environments were paired with greater electrodermal reactivity (EDA) in the individual (Subotnik et al, 2012).…”
Section: Moderators Of Criticism-behavior Problem Linksmentioning
confidence: 99%
“…EDA is considered to be a stable index of the activation of the sympathetic nervous system (Dawson et al 2007), "both among patients with schizophrenia and among those in the normal population [sic] (e.g. Schell et al 2002)" (Subotnik et al 2012(Subotnik et al , p. 1035. To our knowledge, EDA activity has not been put to use in situ in urban environments for the monitoring psychophysiological arousal of people living with a diagnosis of psychosis.…”
Section: The 'Bio' In Urban Mental Healthmentioning
confidence: 99%
“…Electrodermal activity has been intensively studied, as reflecte by the 1973 book Electrodermal Activity in Psychological Research [46]. Several different applications of EDA have been used in diverse fields psychologists measured the elicited EDA in subjects that were shown pictures of spiders and snakes shortly and demonstrated that consciousness is not required to show fear responses [41]; in medicine, symptoms of mental pathologies like schizophrenia have been predicted using EDA measures [53]; and, more recently, it is neuroscience where EDA have served as a useful research tool [55]. Furthermore, in [34,56] we can see how EDA is now being also used in neuromarketing and consumer neuroscience, showing that its potential applications are broad.…”
Section: The Expression Of the Emotions In Man And Animalsmentioning
confidence: 99%